THE INDONESIAN DPD'S ROLE AND POTENTIAL AS A LABORATORY OF SUBNATIONAL PARLIAMENTARY DIPLOMACY - Muhammad Fajhriyadi Hastira (Journal Pena Wimaya, 2026)
The development of global diplomacy reveals an increasing role for subnational actors in international relations, alongside the strengthening of decentralization and multilevel governance. In Indonesia, this phenomenon creates an opportunity for the Regional Representative Council (DPD RI) to contribute by representing regional interests. This study aims to analyze the position, potential, and limitations of the DPD in Indonesia's subnational diplomacy, employing a descriptive qualitative approach that integrates the theories of paradiplomacy and parliamentary diplomacy. The findings reveal that the DPD has significant potential to serve as a laboratory for paradiplomacy, particularly through its coordinative, advocacy, and facilitative roles in promoting regional interests with an international dimension. However, this role has not been optimized due to limitations in formal authority, the lack of institutionalized mechanisms for region-based diplomacy, and the dominance of executive actors and the DPR in the national diplomatic structure. This study concludes that strengthening the role of the DPD requires regulatory adjustments, enhanced collaboration among the DPD, DPR, and the MOFA, and the development of a diplomatic agenda based on regional strengths. Theoretically, this study contributes to the enrichment of subnational parliamentary diplomacy studies, and practically offers policy directions towards a more inclusive and multilevel Indonesian diplomacy.